Study of Structure and Electrochemical Properties of LaFeO3 and La2FeO4 as Electrode Materials for Super-Capacitor Application - Harish Verma; Pramod Kumar; Bhaskar Bhattacharya; Shail Upadhyay (Proceedings)
Perovskite oxides have introduced a new advancement in the field of energy storage technologies, because of their outstanding properties [...]